2013
DOI: 10.1177/1359104513492747
|View full text |Cite
|
Sign up to set email alerts
|

Self-reported peer victimization and suicidal ideation in adolescent psychiatric inpatients: The mediating role of negative self-esteem

Abstract: The current study investigated relationships among self-reported peer victimization, suicidality, and depression in adolescent psychiatric inpatients. Sixty-seven adolescent psychiatric inpatients at a Midwestern children's hospital completed measures of bullying and peer victimization, suicidal ideation, and depression during their inpatient stay. Analyses indicated significant moderate correlations among victimization, suicidal ideation, and depression in adolescents. Results from mediational analyses found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 31 publications
1
11
0
3
Order By: Relevance
“…Bullying victimization is a major global public health problem among adolescents that has been linked to a number of behavioral and emotional problems including anxiety (Cohen and Kendall, 2015), depression (Cole et al, 2014;Hamilton et al, 2016), loneliness (Campbell, 2013;Murphy et al, 2015;Storch and Masia-Warner, 2004), social withdrawal (Dill et al, 2004;Runions and Shaw, 2013), low self-esteem (Fredstrom et al, 2011;Jones et al, 2014;Tsaousis, 2016), as well as poor psychosocial adjustment (Nansel et al, 2001). Various meta-analytic studies have also found support for the link between bullying victimization and the onset of depressive symptoms and internalizing problems (Reijntjes et al, 2010;Ttofi et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Bullying victimization is a major global public health problem among adolescents that has been linked to a number of behavioral and emotional problems including anxiety (Cohen and Kendall, 2015), depression (Cole et al, 2014;Hamilton et al, 2016), loneliness (Campbell, 2013;Murphy et al, 2015;Storch and Masia-Warner, 2004), social withdrawal (Dill et al, 2004;Runions and Shaw, 2013), low self-esteem (Fredstrom et al, 2011;Jones et al, 2014;Tsaousis, 2016), as well as poor psychosocial adjustment (Nansel et al, 2001). Various meta-analytic studies have also found support for the link between bullying victimization and the onset of depressive symptoms and internalizing problems (Reijntjes et al, 2010;Ttofi et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The importance of personal factors in the context of bullying was described in a study by Sapouna et al 43 Individual characteristics determine whether a person remains a victim of bullying over time. Jones et al 44 showed that in adolescents, a negative self-esteem increases the association between peer victimization and suicidal ideation. Another important individual characteristic is the victims' causal perception of why they are bullied.…”
Section: Discussionmentioning
confidence: 98%
“…Teens evaluate themselves based on the feedback they receive from their peers, which explains why negative self-esteem acts as a mediating variable between peer victimization and the other indicators of psychological adjustment (social self-efficacy and social anxiety), mainly in adolescence, a identity confusion phase where the decreased levels of self-esteem increases the vulnerability to psychological disorders (van Tuijl et al, 2014). The mediating role of negative self-esteem as a cause of other problems of psychological adjustment, such as anxiety or depression, has been recognized in recent studies (Ferro and Boyle, 2014; Jones et al, 2014). Some authors explain this relationship in terms of the attributions of the victims, who tend to blame themselves for their personal characteristics (what is known as characterological self-blame), causing them great emotional distress (Janoff-Bulman, 1979).…”
Section: Discussionmentioning
confidence: 99%